Analysis of Elbow Effect on the High Pressure Gas Pipe. (July 2020) - Zhang, Jianhua; Huang, Haifeng; Hu, Kun; Zhang, Ping
Abstract: For the problem of the pressure drop loss and the equivalent length calculation of elbows in submarine high pressure pipelines, the flow processes of ultra-high pressure gas in 90° elbows were numerically simulated by the way of CFD. The inner flow area was meshed with structured hexahedral grid, and by means of the numerical solution to deal with the RANS equations closed by RNG k-ε turbulence model, the flow field characteristics inside the pipe was studied, and the pressure distribution was obtained. The calculated results are consistent with the numerical simulation and model experiment results carried out by other scholars. Simulation results show that the total pressure loss of the pipe will be increased greatly due to the partial pressure loss caused by elbows. Besides, the feasibility and availability of simulating the flow characteristics of the ultra-high pressure gas inside the elbows by RNG k-ϵ turbulence model were verified.